The obsession with revenge and vengeance in pre-Islamic poetry - Badr, Iman; Idan, Ikhlas (Al-Adab Journal, 2024)
Revenge is a social phenomenon that accompanied the life path of pre-Islamic society until it became their souls, from which they were inspired by the pride of defiance and the dignity of confrontation. Revenge poetry in pre-Islamic Arabic poetry occupied great importance, and special attention due to its novelty and widespread prevalence. The word revenge indicates the infliction of some kind of punishment against a person. Certain with specific motives arising from a force of anger.The collections of poets were full of talk about revenge, whether it was revenge for the brother, the son, the father, the mother, or others, but revenge for the brother was more present in the collections of poets, as the death of a brother was considered one of the severe calamities that were difficult to bear and avoid, and (the psychological factor had a great effect in stirring feelings. The brother and the family of the murdered person towards the pursuit of revenge, as the brother reaches a desperate stage after the killing of his brother, and falls into the captivity of pain and sorrow from which he cannot escape unless he defeats the killer and takes revenge on him, thus overcoming all the obstacles that stand before him that prevent him from achieving what they aspire to. To him, because if he does not achieve his goal, he will inevitably fall into disgrace and disgrace, according to the principles of pre-Islamic society and its laws that relate to the principle of realizing revenge.Poets who have tasted the bitterness of sadness shed tears and continuous weeping, perhaps they contain the bitterness of the difficult situation, and they succeed in absorbing the estrangement of the soul, to justify the poets’ launch into lamentation that includes remembrance and praise for the deceased, by preparing a psychological ground to prove the values, which are the focus of existence. Therefore, we notice their striving to consolidate These values are in their society, and the focus of this circumstance was embodied in many pre-Islamic poets.